Extração de contornos de telhado de edifícios no espaço-objeto baseada em snakes e programação dinâmica a partir de TIN/laser e imagens aéreas de alta resolução - Fazan, Antonio Juliano [UNESP] (2011)
This research presents a semi-automatic method for rectilinear building roof contours extraction, based on the integration of high resolution aerial imagery taken from dense urban scenes and light detection and ranging (LiDAR) data. 3D information derived from LiDAR data and the high roof contour delineation accuracy in the aerial imagery can be combined in order to accurately extract the building roof contours. The proposed method is organized as an optimization problem, in which a mathematical model is used to represent the building roof contours in an object-space reference frame. The global solution for the resulting problem is found by using the dynamic programming optimization technique and corresponds to 3D polygons describing the building roof contours. The mathematical model describing a building roof contour is firstly expressed in an image-space reference frame, by using a snakes energy function, and then, the resulting snakes-based mathematical model is totally reformulated in such a way to describe building roof contours directly in an object-space reference frame, by integrating the LiDAR data represented as a triangulated irregular network (TIN) structure...